2022
DOI: 10.1039/d1cc06348k
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of closo-dodecaiodododecaborate in 2-hydroxypropyl-γ-cyclodextrin prevents hemolysis

Abstract: Na2B12I12 has many of the properties desired by an X-ray contrast agent but is lethal at the concentrations needed for medical imaging. We demonstrate here that PBS solutions with >...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…160,161 Hollow and Johnstone have recently reported that the complexation of the iodinated cluster with a permethylated γ-CD derivative prevents hemolysis, due to complexation. 160 The authors also reported the XRD structure of the B 12 I 12 2− •γ-CD complex which bears close similarity to that of B 12 Br 12 2−…”
Section: Potential Applications Of Large Anion Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…160,161 Hollow and Johnstone have recently reported that the complexation of the iodinated cluster with a permethylated γ-CD derivative prevents hemolysis, due to complexation. 160 The authors also reported the XRD structure of the B 12 I 12 2− •γ-CD complex which bears close similarity to that of B 12 Br 12 2−…”
Section: Potential Applications Of Large Anion Bindingmentioning
confidence: 99%
“…The largest dodecaborate anion, B 12 I 12 2− , is also a promising X-ray contrast agent for medical diagnostics (owing to the heavy-atom content) but it is known to induce hemolysis at high mM concentrations. 160,161 Hollow and Johnstone have recently reported that the complexation of the iodinated cluster with a permethylated γ-CD derivative prevents hemolysis, due to complexation. 160 The authors also reported the XRD structure of the B 12 I 12 2− ·γ-CD complex which bears close similarity to that of B 12 Br 12 2− ·γ-CD (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the binding sites in HPC are rather undefined, while in γ‐CD the well‐defined cavity allows for a good size‐match [9] with SiW further facilitating binding. Notably, binding affinities to γ‐CD and functionalized Hydroxypropγl‐CD (the macrocyclic equivalent to HPC) are expected to be similar, [36] which points at the insignificance of chemical differences between HPC and γ‐CD for the binding in comparison to their topographical differences.…”
Section: Figurementioning
confidence: 99%
“…Boron-containing compounds have application potential in pharmaceutical chemistry, with boron neutron capture therapy being the most prominent example . Recently, a new cell-biological as well as medicinal-chemical application line has been documented for icosahedral dodecaborates B 12 X 12 2– (X = H, Cl, Br, and I; Figure a), because their superchaotropic ionic character enables their use as broadband membrane carriers, that is, they enable cellular uptake of a wide range of otherwise impermeable hydrophilic molecules, including amino acids, neurotransmitters, peptides, and drugs. , This, combined with their chemical inertness, , high water solubility, ,, and high biocompatibility, ,,,,, defines a new research area in chaotropic inorganic cluster chemistry. Accordingly, it is of interest to investigate how variations in the boron cluster structure and topology affect their chaotropic character and, thus, their potential membrane carrier activity.…”
Section: Introductionmentioning
confidence: 99%